(untitled) (TAMADDUN NURI JURNALI, 2025)
This article is dedicated to the study of cumulative tales, which are an important part of Uzbek folk oral literature, using a holistic methodology. Additionally, with the help of a holistic methodology, the structure and semantic features of these tales are thoroughly examined, and their folkloristic value is assessed.